2004
DOI: 10.1016/j.cell.2004.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Histone Demethylation Mediated by the Nuclear Amine Oxidase Homolog LSD1

Abstract: Posttranslational modifications of histone N-terminal tails impact chromatin structure and gene transcription. While the extent of histone acetylation is determined by both acetyltransferases and deacetylases, it has been unclear whether histone methylation is also regulated by enzymes with opposing activities. Here, we provide evidence that LSD1 (KIAA0601), a nuclear homolog of amine oxidases, functions as a histone demethylase and transcriptional corepressor. LSD1 specifically demethylates histone H3 lysine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

61
3,504
1
25

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 3,703 publications
(3,591 citation statements)
references
References 65 publications
61
3,504
1
25
Order By: Relevance
“…Shi et al showed that LSD1, a nuclear amine oxidase, found in several histone deacetylase complexes, specifically demethylates mono-or di-methyl-H3-K4 (H3-K4me1 or H3-K4me2, respectively) in a flavin adenine dinucleotide-dependent oxidase reaction (Shi et al, 2004). However, this type of enzyme cannot demethylate tri-methylated residues.…”
Section: Functions Of Jumonji Family Proteins In Transcription and Chmentioning
confidence: 99%
“…Shi et al showed that LSD1, a nuclear amine oxidase, found in several histone deacetylase complexes, specifically demethylates mono-or di-methyl-H3-K4 (H3-K4me1 or H3-K4me2, respectively) in a flavin adenine dinucleotide-dependent oxidase reaction (Shi et al, 2004). However, this type of enzyme cannot demethylate tri-methylated residues.…”
Section: Functions Of Jumonji Family Proteins In Transcription and Chmentioning
confidence: 99%
“…In contrast, Lsd1 (KDM1A), a flavin‐containing amino oxidase, was the first enzyme identified that had the ability to demethylate mono‐ and dimethylated histone H3 lysine 4 histone substrates 27. Subsequently, a second, larger family of Fe (II) and 2‐oxoglutarate oxygenases, which contain a catalytic domain which has been termed the ‘Jumonji domain’, was identified 28.…”
Section: Histone Methylationmentioning
confidence: 99%
“…There are many examples of N(itrogen)-methylations (of arginine, lysine, glutamine, asparagine, histidine residues, and the amino group at the N terminus) in the cell. While it is not certain that all N-methylations are reversible, recent discoveries showed that a human nuclear peptidyl arginine deiminase, PAD4, antagonizes methylation on the arginine residues by converting arginine to citrulline [92][93][94] (Figure 5); a human nuclear amine oxidases, LSD1, functions as a histone di/mono-methyl-lysine demethylase via an oxidation reaction [95][96][97]; and JmjC domain-containing hydroxylase-like proteins are able to demethylate mono-, di-, or tri-methylated lysines [98,99], which was first proposed for S. pombe Epe1 [100].…”
Section: Demethylation By Oxidation or Hydroxylationmentioning
confidence: 99%
“…LSD1 (also known as BHC110), named after protein lysine-specific-demethylase 1 [95], is found in histone modification complexes that control cell-specific gene expression. Within these complexes, REST (RE1-silencing transcription factor) corepressor CoREST enables LSD1 to demethylate nucleosomes [96,97], while BHC80 (BRAF-HDAC complex) inhibits LSD1 activity [96].…”
Section: Lsd1mentioning
confidence: 99%
See 1 more Smart Citation